2020
DOI: 10.1038/s41598-020-74488-w
|View full text |Cite
|
Sign up to set email alerts
|

Sub-clustering in skeletal class III malocclusion phenotypes via principal component analysis in a southern European population

Abstract: The main aim of this study was to generate an adequate sub-phenotypic clustering model of class III skeletal malocclusion in an adult population of southern European origin. The study design was conducted in two phases, a preliminary cross-sectional study and a subsequent discriminatory evaluation by main component and cluster analysis to identify differentiated skeletal sub-groups with differentiated phenotypic characteristics. Radiometric data from 699 adult patients of southern European origin were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 33 publications
5
16
1
Order By: Relevance
“…In the present study, the most severe sub-phenotype of skeletal Class III malocclusion was observed in C1, which accounted for the smallest proportion of the sample population (18.4%) among all subgroups, similar to the case in previous studies [ 26 , 33 , 34 , 41 ]. However, in this case, gender distribution was proportional.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the present study, the most severe sub-phenotype of skeletal Class III malocclusion was observed in C1, which accounted for the smallest proportion of the sample population (18.4%) among all subgroups, similar to the case in previous studies [ 26 , 33 , 34 , 41 ]. However, in this case, gender distribution was proportional.…”
Section: Discussionsupporting
confidence: 90%
“…The highest anterior facial height was also observed in C1, but the mandibular plane was normal. The low frequency of severe Class III malocclusion observed here and in several previous studies may be due to the selection process: the selection of an ANB <1 or 0 [ 26 , 33 , 34 , 41 ] and a Wits appraisal <0 or −2 mm [ 26 , 33 , 34 ] may allow for the inclusion of less severe skeletal Class III malocclusion subjects.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations